Correction: Characterizing chain processes in visible light photoredox catalysis - Cismesia, Megan A. (Chem Sci, 2015)
Correction for ‘Characterizing chain processes in visible light photoredox catalysis’ by Megan A. Cismesia et al., Chem. Sci., 2015, DOI: 10.1039/c5sc02185e.